L’après-guerre du peuple ? La Grande-Bretagne sous les Travaillistes vue par Britain To-day (1945-1950) - Alice Byrne (Revue LISA)
Britain To-day is the title of a magazine published by the British Council from 1939 to 1954. This form of cultural propaganda was originally intended as a riposte to anti-British propaganda of the 1930s. The immediate post-war years were a period of transition as the periodical adapted to peace-time conditions. Britain To-day continued to present an image of the UK which aimed at making its overseas readers supportive of British policy. This entailed a departure from the war-time editions’ concern with reconstruction and social reform. Difficult post-war conditions, which made US support of primary concern, led Britain To-day to downplay the Labour government’s programme of reforms. Economic and commercial concerns came to the fore as Britain To-day championed Britain’s determination to overcome austerity and provided discreet support for British exports.